ANALYSIS OF STRATEGIES FOR DEVELOPING COOPERATIVES, COMMUNITY EMPOWERMENT AND MICRO SMALL AND MEDIUM ENTERPRISES (MSMEs) IN BANJARNEGARA DISTRICT, CIWANDAN DISTRICT, CILEGON CITY - Harsono, Pramudi; Oktaviani, Nadila; Salma, Adilla; Kusuma, Putri Wijayanti; Maharani, Adella; Sugari, Tegar (Yayasan Education and Social Center, 2024)
Managing a cooperative based on family economics and mutual cooperation really requires hard work and double enthusiasm. Cooperatives are seen as the right business entity to grow and support popular economic growth. Cooperatives are a pillar of the Indonesian economy. Cooperatives have various obstacles in terms of running their business and quite a few cooperatives do not grow despite the lack of need for information technology to support business processes and the lack of financial support (Wahid Iswara & Iswari, 2007). Of course, a strategy for potential cooperative development is needed. It is time for regional government institutions at sub-district level, such as those in Banjrnegara sub-district, Ciwanda sub-district, Cilegon city, to establish a cooperative institution to provide shelter for businesses and MSMEs. Building quality businesses such as Micro, Small and Medium Enterprises (MSMEs) are three different aspects but have the same aim, namely efficiency and increased results. Apart from that, in facing business challenges in the digital era, MSMEs need to adapt and be dynamic in technological developments. The goal of establishing a cooperative is of course to accommodate production results and savings and loan institutions based on a people's economy. This is of course accompanied by MSME coaching which includes exposure, training through practice and mentoring. This method is quite appropriate to apply because the results of the activity show that the target audience has been able to identify HR empowerment through mentoring. Furthermore, in dealing with obstacles that arise in human resource management, the role of local government in the form of intensive and continuous training is needed. This makes us aware that it is very important to carry out sustainable planning in industrial areas in rural areas, so that villages can develop through industry without experiencing the negative impacts mentioned previously